Squatting in Rio de Janeiro Constructing Citizenship and Gender from Below (Edition 1) - Wittger, Bea (transcript Verlag, 2017)
The Brazilian Constitution provides a remarkable set of social rights, including the right to housing. Despite this fact, struggles for decent living conditions have become key issues in the daily urban lives of many people in Brazil. Contesting the differentiated access to housing, social movements occupy empty buildings in the cities to challenge historically-rooted and excluding urban politics. Exploring the occupants' agency, Bea Wittger draws attention to the important role of female actors within the buildings. Through oral histories of participants of two squats in Rio de Janeiro, the book delivers a deep insight "from below" into their own perspectives on citizenship and gender.